On the Savage Side - McDaniel, Tiffany (New York : Alfred A. Knopf, 2022)
"Six women - mothers, daughters, sisters - gone missing. When the first is found floating dead in the river, it reveals the disturbing truth of a small Ohio town. Inspired by the unsolved murders of the Chillicothe Six, this harrowing and haunting novel tells the story of two sisters, both of whom could be the next victims, from the internationally-bestselling author of Betty"--.
New Book 2023 Spring.
Keywords: Sisters; Mystery; Missing persons; Ohio; Novels; Mystery fiction